Selection of lactic acid bacteria for exopolysaccharide production - Emnace, Ivy C.; Dizon, Erlinda I. (Annals of Tropical Research, 2018)
An important source of natural alternative to commercial additives that are commonly extracted from plants and animals is the exopolysaccharide (EPS) produced by lactic acid bacteria (LAB). A screening for EPS production by Lactobacillus delbrueckii, Lactobacillus rhamnosus NBRC 3425 and Weisella paramesenteroides was conducted to identify which among these three LAB would produce the highest yield of EPS. The test organisms were grown in a Semi-defined Medium (SDM) of Sanchez et al (2006) with some modifications. EPS production was confirmed by the formation of precipitate after mixing the broth medium with 95% absolute ethanol. Results of total sugar analysis by phenol-sulfuric acid assay revealed that estimated EPS yield of L. rhamnosus NBRC 3425 was significantly higher at p<0.05 than those of W. paramesenteroides and L. delbrueckii ssp. lactis with values of 0.1355g/L, 0.0652g/L and 0.0544g/L, respectively even though their viable count did not differ significantly from each other. Correspondingly, the pH of L. rhamnosus NBRC 3425 media was also significantly higher (pH 4.03) than L. delbrueckii (pH 3.60) and W. paramesenteroides (pH 3.83).